Determinants Of The Incidence Of Acute Respiratory Infections (Ari) In Toddlers In The Working Area Of The Health Centers Simpang Pandan, Tanjung Jabung Timur Regency In 2022 - Fitria Eka Putri; Cindy Syah Putri; Rumita Ena Sari; Hubaybah; Oka Lesmana (CV. AFDIFAL MAJU BERKAH, 2022)
Disease (acute respiratory infection) Ari is one type of Environmental-based infectious diseases. In Indonesia, cases of Ari always ranks first cause of infant mortality and the prevalence of Ari disease in Jambi province amounted to 3.2% and in Tanjung Jabung Timur amounted to 4.44%. ISPA in East Tanjung Jabung regency is a disease trend every year. In general, the risk factors for ARI are physical environmental factors, host/host factors, agent factors and social environmental factors. The type of research used is quantitative research with cross sectional design. This study aims to find the relationship between the variable occupancy density, floor type, wall type, ceiling of the house, lighting, smoking family members, maternal knowledge with the incidence of ARI in toddlers. The population in this study were toddlers in the Working Area of the Simpang Pandan Health Center and the sample of this study was 103. Sampling technique in this study using Stratified Random Sampling technique. How data collection is done by interviews, observations, and measurements using tools. The results showed that there is a relationship between : occupancy density (P - value=0.003 and PR = 1.976), floor type (p= 0.014 and PR = 1.874), wall type (p=0.020 and PR = 1.852) lighting (p=0.018 and PR = 1.790), smoking family members (p= 0.020 and PR = 1.852 ) and maternal knowledge (P-value=0.035 and PR = 1.678) with acute respiratory infections in toddlers. While the variables that are not related to the incidence of ARI in this study is the variable ceiling of the House (p-value = 0.968 and PR = 1.080). It is recommended that family members do not smoke in the house, pay attention to the residential density of the House, home lighting, and the type of floor in the House.